ANALYSIS OF THE INFLUENCE OF PERCEPTIONS OF USEFULNESS, PERCEPTIONS OF USEFULNESS, PERCEPTIONS OF SYSTEM SECURITY, AND QUALITY OF SERVICE ON SATISFACTION IN USING ACCOUNTING INFORMATION SYSTEMS IN THE SHOPEE LOAN APPLI - Elizabeth, Jessica; Rachmawati, Lia; Fanzuri Yusuf, Hamzah (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to analyze the effect of perceptions of usefulness, convenience, system security and service quality on the satisfaction of using accounting information systems in the shopee application. This type of research used is quantitative research. The data used is primary data with data collection techniques, namely questionnaires and literature study. The data analysis method used is the instrument data test, classical assumption test, multiple linear regression, and hypothesis testing. The results showed that perceived usefulness, convenience, system security and service quality did not simultaneously influence user satisfaction because the significance value was 0.096, but service quality had a positive and significant effect. Keywords: Perceived usefulness, Perceived Convenience, Perceived System Security, Service Quality, User Satisfaction.